Epigenetic targeting in lymphoma. (1st July 2020) - Booth, Stephen; Collins, Graham
Summary: Despite considerable progress in the treatment of patients with lymphoid malignancies in recent decades, the prognosis of patients with relapsed or refractory lymphomas often remains disappointing. Increasing evidence has established the relevance of epigenetic alterations in the pathogenesis of lymphoid malignancies, and a succession of agents has been evaluated in clinical studies with varying efficacy. In the present review, we outline the importance of epigenetic modifications in lymphoma biology and discuss the published experience with epigenetic modifying agents by lymphoma subtype before considering ongoing clinical studies in this area.